Aplikasi Teknologi Nanoenkapsulasi untuk Melindungi Senyawa Bioaktif Bahan Pangan - Wicaksono, Dani Satrio; Nurdyansyah, Fafa (Program Studi Teknologi Pangan, 2021)
ABSTRACTÂ Bioactive compounds are components in plants that have health benefits such as antioxidants, anticancer, anti-inflammatory and antibacterial activities. However, bioactive compounds are easily damaged due to processing such as heating, drying, changes in pH, temperature and environment, thereby reducing their activity and functional value. One technique that can be used to reduce the level of damage for bioactive compounds is to use nanoencapsulation technology. Aplication of nanoencapsulation is used to protect bioactive components of food ingredients due to processes and environmental changes. Nanoencapsulation is one of the most effective technologies because of its ability to entrap bioactive compounds in the coating matrix, namely biopolymer components that are nanoparticle-sized so that they are more resistant to environmental changes and processing. Encapsulation can be used by various methods such as emulsification, coacervation, and inclusion. The coating material that will form the wall or capsule generally consists of carbohydrate, protein and fat polymers. The effectiveness of nanoencapsulation in protecting bioactive compounds depends on the selection of the nanoencapsulation method and the type of coating material used. The results showed that the nanoencapsulation process could increase or maintain the stability of the bioactive components.